Integrating Problem-Based Learning (PBL) in Mathematics Method Course - Zamri, S.N.A.S.; Lee, S.E. (2005)
In this era of rapid technological innovation, institutions of higher learning including University of Malaya are faced with the challenge to develop highly qualified and trained graduates. Since the current innovations call for new competencies, skills and knowledge from our graduates, an alternative approach to teaching in higher learning institutions is inevitable. In this regard, Problem-Based Learning (PBL) has emerged as a promising approach to accomplish these goals. In this study we examined the implementation of Problem Based learning in a Mathematics Method course. Specifically, the objectives are to investigate students’ attitudes pre and post PBL session, students’ activities in the PBL session and students’ perceptions towards the PBL session. The participants for this study were 63 students enrolled in an undergraduate mathematics method course. The assessment results indicate that PBL method has an overall positive impact on the Mathematics Method students’ attitudes, activities and perceptions towards Problem-Based Learning.